Monica - Argyriou, Dimitris (Germany Greece, 2016)
Monica wanted to become hair dresser, when she was young. Things went wrong…and this is her story. (Based on a real interview with a human trafficking victim.)
Verzio Film Festival Submission
Keywords: Documentary films